The first In(OTf)3-catalyzed conversion of kinetically formed homoallylic alcohols into the thermodynamically preferred regioisomers: Application to the synthesis of 22α-sterols - Loh, T.-P. (2014)
10.1002/1521-3773(20010803)40:153.0.CO;2-V